The Influence of Compensation and Work Environment on Employee Performance Mediated by Employee Engagement at PT. XYZ - Pratiwi Noviana; Furqon Syarief Hidayatulloh; Yunus Triyonggo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Technology has advanced with the use of AI, but human resources, as the primary asset in achieving company goals, remain irreplaceable. The current performance problem is low employee performance. The purpose of this study is to analyze the effect of compensation on employee performance, compensation on employee engagement, the work environment on employee performance, the work environment on employee engagement, and employee engagement on employee performance. The number of respondents was 200 respondents. The research sample was determined using stratified random sampling. Data analysis in this study used SEM PLS to determine the effect of independent variables on the dependent variable. The SEM PLS analysis results indicate that compensation affects employee engagement, the work environment has a positive effect on employee performance, and employee engagement has a positive effect on employee performance. However, compensation hurts employee performance, while the work environment does not affect employee engagement. The AHP analysis results indicate that compensation is the primary factor in improving employee performance. The conclusion of the study states that although compensation has a negative effect on employee performance, if it is not fulfilled it will cause job dissatisfaction, therefore employee compensation must be considered and increased by employees in order to create a bond between employees and the company which will improve employee performance in the future.